Effect of ticagrelor versus clopidogrel after implantation of drug-eluting stents guided by either intravascular ultrasound or angiography in patients with acute coronary syndrome—propensity score matching analysis - Yinan Zhao; Yuxin Yang; Lei Guo; Dapeng Shen; Zhichao Dong; Yajuan Lin; Hao Liu; Yushan Wei; Bo Zhang (BMC Cardiovascular Disorders, 2024)
Abstract Background The effect of different dual antiplatelet therapies on thrombotic events on the background of intravascular ultrasound (IVUS) guidance is unclear. We investigated whether ticagrelor can provide any additional benefit to clopidogrel in reducing thrombotic events in acute coronary syndrome (ACS) treated with drug- eluting stent (DES), when guided by IVUS or not. Methods A total of 5,666 ACS patients who underwent DES implantation and who were discharged on dual antiplatelet therapy were enrolled and grouped according to the use of IVUS or not. Each group was subdivided into two subgroups according to the type of P2Y12 inhibitor used after discharge. Propensity score matching (PSM) was used between the IVUS and no-IVUS groups. Covariate adjustment of Cox proportional hazards model was used between the ticagrelor and clopidogrel groups. Thrombotic event at 12 months was compared in groups separately. Results After PSM, 12-month follow-up data were available for 1,174 patients. Major adverse cardiac events (MACE) were less frequent in the IVUS-guided group (2.2% vs. 4.3%, P = 0.081) with a trend toward statistical significance. Comparison of antiplatelet regimens revealed significantly fewer major adverse cardiac and cerebrovascular events (MACCE) with ticagrelor in the entire PSM cohort and angiography-guided subgroup (2.9% vs. 5.7%, P = 0.035; 3.1% vs. 6.4%, P = 0.020, respectively). Among patients in the IVUS-guided group the outcome was comparable (2.5% vs. 4.4%, P = 0.312). Ticagrelor was associated with increasing bleeding incidence in the entire PSM cohort (1.3% vs. 3.3%, P = 0.030), mainly due to Bleeding Academic Research Consortium type 2 bleeding (0.7% vs. 2.6%, P = 0.010). The results were consistent after covariate adjustment of Cox proportional hazards model. Conclusion The comparison of ischemic benefit between ticagrelor and clopidogrel was similar in patients receiving IVUS guidance during stent implantation, probably due to the precise implantation of IVUS. Multicenter, randomized studies should be performed to validate this conclusion.